Analisis Potensi Budidaya Rumput Laut dan Strategi Ekowisata Pantai Mutiara, Kabupaten Trenggalek, Provinsi Jawa Timur - Bima Satya Adhiluhung; Dyaz Ayu Marcela; Michellia Alba Camelia Az-Zahra; Sean Ilhan Ibrahim; Sonia Ardianti (Syntax Corporation Indonesia, 2024)
Sustainable ecotourism management can affect the state of the community around the area. A total of approximately 15 beaches are managed in Trenggalek Regency. This study aims to analyze the suitability of the water parameters of Prigi Bay, Trenggalek as a seaweed cultivation location and get the right strategy in the development of Mutiara Beach ecotourism, Trenggalek Regency. The data collection method carried out is by combining questionnaire dissemination techniques, direct interviews with resource persons, and field observation. The questionnaire procedure was carried out using the slovin method to determine the number of respondents by applying accidental sampling. Field observation procedures were carried out to measure water quality parameters at 4 observation stations. The research was conducted in May 2024. The parameters measured for seaweed cultivation include temperature, brightness, current velocity, pH, salinity, dissolved oxygen, and water depth. The research analysis uses quantitative descriptive with the Inverse Distance Weighted (IDW) Interpolation technique to analyze data on the suitability of seaweed cultivation locations and supply demand analysis which will later be used as a SWOT analysis to analyze ecotourism strategies. The results of the study on the potential of seaweed cultivation showed that the water temperature ranged from 30⁰ C-31.4⁰ C, brightness 50-142 cm, current velocity 0.08-0.013 m/s, pH 7.22-7.76, salinity 30-32 ppt, dissolved oxygen 9.4 mg/l, and water depth 9-15 m. So based on the thematic map of land suitability, stations 1 & 2 are not suitable for seaweed cultivation while stations 3 & 4 are very suitable for cultivation. Meanwhile, in the ecotourism strategy, the development results are obtained in accordance with the SO strategy. Visitors and managers prioritize advantages and opportunities as an alternative to development.